COMMUNICATION POLICY OF THE CENTRAL BANK IN THE CONTEXT OF RESTORATION OF SOCIAL TRUST FOR THE FINANCIAL SECTOR OF THE COUNTRY - Кривич, Яна; Сердюк, Катерина (Socio-economic relations in the digital society, 2019)
The article substantiates the issue of improving the communication policy of the central bank, which would help to monitor the expectations of financial sector agents and adapt their policies closer to their expectations. This question is important in the conditions of low public trust in the central bank. This paper encompasses conceptual framework for understanding the central bank’s communications policy as an indicator of raising public confidence. It has been highlighted that decline in trust in the central bank means that market participants have doubts about the consistency of monetary policy, its objectives and the professionalism of management. The implementation of a quality communication policy is very important, as the central bank can build monetary policy not only on the basis of real indicators, but also on expectations, and at the same time to improve the trust of the population. Therefore, the issue of conducting high-quality communication policy by central banks is becoming more acute, which would help to realize all aspects of its activities, identify the expectations of financial market participants and adapt their policies as close as possible to their expectations, first of all, to improve public confi dence. The National Bank of Ukraine is a modern, open and independent central bank that integrates with the European community of central banks and strives to maintain public confidence. In its strategy, the Central Bank of Ukraine recognizes communication as an integral part of its activities aimed at achieving its goals. The authors of the article analyze the essence of the «communication policy» and investigate its genesis, determine the role of communications in the activities of the central bank and establishe the connection of public trust to the central bank and its communication policy.